Implikasi Penetapan Adat Basandi Syarak - Syarak Basandi Kitabullah dalam Undang-Undang Nomor 17 Tahun 2022 tentang Sumatra Barat Terhadap Politik Hukum Pemerintah Daerah Sumatra Barat - Adam Alfarid; Chindy Trivendi Junior; Putri Ramadani (Jurnal Hukum Lex Generalis, 2022)
The provisions of Article 5C of Law No. 17 of 2022 concerning West Sumatra Province contain the Adat Basandi Syarak - Syarak Basandi Kitabullah (ABS-SBK) which is a Minangkabau traditional philosophy. However, the determination of the Minangkabau traditional philosophy does not yet have a clear benchmark, thus making the legal politics of the West Sumatra local government seem to favor one particular group. It is feared that the philosophy based on syarak will form a sharia-based regional regulation. In addition, the traditional philosophy leads to a custom, namely Minangkabau, which raises questions about the position of the Mentawai in West Sumatra who are not Minangkabau indigenous peoples.